Transferencias y luchas culturales transatlánticas: feminismo, librepensamiento y redes masónicas entre Europa y América (1860 - 1910) - Mollès, Dévrig (2025)
The Atlantic Revolutions of the nineteenth-century were characterized, among others things, for the empowerment of people and Civil Society, the secularization of the State and the emancipation of the female gender. This introductory text takes on these common rhythms from the notion of International Public Opinion, from the interaction between three international spheres: Masonic networks, Freethinking and Feminism. The empirical part of this text seeks a global perspective, focusing on Latin America, particularly the Argentine and Brazilian cases, between 1860 and 1910. In conclusion, this essay proposes theoretical tools for analyzing the Geo-culture in the Modern World-System and System-Masonic World, in view of future developments.